2012
DOI: 10.5014/ajot.2012.004010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Classroom Modification on Attention and Engagement of Students With Autism or Dyspraxia

Abstract: Students with autism display sensory sensitivities to environmental stimuli that affect their attending and engagement in classroom learning activities. The purpose of the study was to determine whether attending of 4 male students, ages 13-20, increased after the installation of sound-absorbing walls and halogen lighting. The multiple single-subject, mixed-method design, AB(B+C), included a 2-wk baseline and two intervention phases: 2 wk after sound-absorbing wall installation using the Owens Corning Basement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(74 citation statements)
references
References 19 publications
3
70
0
1
Order By: Relevance
“…With respect to intervention studies, no differences in improvement were observed between ASD and DCD groups in attention (Kinnealey et al, 2012; Cosper et al, 2009) or IQ (Kozulin et al, 2010). It is possible that the capacity to train and improve in several domains, especially cognition, is similar for these conditions.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…With respect to intervention studies, no differences in improvement were observed between ASD and DCD groups in attention (Kinnealey et al, 2012; Cosper et al, 2009) or IQ (Kozulin et al, 2010). It is possible that the capacity to train and improve in several domains, especially cognition, is similar for these conditions.…”
Section: Discussionmentioning
confidence: 88%
“…Kinnealey et al (2012) used a quantitative and qualitative mixed-method analysis to explore whether alterations to the sensory environment reduced “non-attending behaviors” in one student with dyspraxia/DCD and three students with ASD. Sound-absorbing walls and halogen lightning were installed in a classroom, and the authors analyzed the frequency of non-attending behaviors captured in videos of class segments.…”
Section: Resultsmentioning
confidence: 99%
“…In the same context, Raca and Dillenbourg () used the synchronization of students' gaze direction and body postures for predicting their self‐reported attention. Attention has been found to be a strong construct of engagement (Kinnealey et al , ; Mundy, Acra, Marshall, & Fox, ). The results showed that students with lower levels of attention were slower in reacting to the teacher than the focused students.…”
Section: Related Work: Utilizing Multimodal Data To Predict Learning mentioning
confidence: 99%
“…These strategies fall into three groupings. First, through modification of the sensory environment, such as changes to noise levels and classroom lighting (Kinnealey et al, 2012) and use of equipment to control sensory inputs, such as headphones (Ashburner, Rodger, Ziviani & Hinder, 2014). Second, task modification such as use of visual schedules (Knight, Sartini & Spriggs, 2015).…”
Section: Introductionmentioning
confidence: 99%